AIE‐Active Difluoroboron Complexes with N, O‐Bidentate Ligands: Rapid Construction by Copper‐Catalyzed C−H Activation. Issue 18 (26th July 2021) - Tan, Guangying; Maisuls, Iván; Strieth‐Kalthoff, Felix; Zhang, Xiaolong; Daniliuc, Constantin; Strassert, Cristian A.; Glorius, Frank
Abstract: The development of organic materials with high solid‐state luminescence efficiency is highly desirable because of their fundamental importance and applicability in optoelectronics. Herein, a rapid construction of novel BF2 complexes with N, O‐bidentate ligands by using Cu(BF4 )2 6H2 O as a catalyst and BF2 source is disclosed, which avoids the need for pre‐composing the N, O‐bidentate ligands and features a broad substrate scope and a high tolerance level for sensitive functional groups. Moreover, molecular oxygen is employed as the terminal oxidant in this transformation. A library of 36 compounds as a new class of BF2 complexes with remarkable photophysical properties is delivered in good to excellent yields, showing a substituent‐dependency on the photophysical properties, derived from the π – π * character of the photoexcited state. In addition, aggregation‐induced emission (AIE) is observed and quantified for the brightest exemplars. The excited state properties are fully investigated in solids and in THF/H2 O mixtures. Hence, a new series of photofunctional materials with variable photophysical properties is reported, with potential applications for sensing, bioimaging, and optoelectronics. Abstract : A novel strategy is developed for the rapid construction of aggregation‐induced emission (AIE) active BF2 complexes with N, O‐bidentate ligands through a copper‐catalyzed cascade CH activation/acyloxylation and difluoroboronation, which avoids the need for pre‐composing the N, O‐bidentate ligands. A library of 36 compounds as a new class of AIE‐active BF2 complexes with remarkable photophysical properties is delivered in good to excellent yields.